Pengaruh profitabilitas, leverage, dan likuiditas terhadap harga saham - Putri, Aisyah Bestari; Hendrani, Ai (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study is to identify whether is an effect of profitability, leverage, and liquidity on stock prices in the food and beverage sub-sector which are listed on the IDX (Indonesian Stock Exchange) for 2018-2021. In this study the independent variables used were the profitability variable using the ROA (Return On Assets) proxy, the leverage variable using the DER (Debt to Equity Ratio) proxy, the liquidity variable using the CR (Current ratio) proxy, and the dependent variable was the stock price variable. Using the closing price. The selection of samples in this study was 15 companies for 4 years so as to produce as many as 60 research samples. The data analysis method used is multiple linear regression analysis. The source of data processing in this study uses the SPSS application. The results of the study show that profitability, leverage, and liquidity have a simultaneous effect on stock prices, variable profitability affects stock prices, leverage has no effect on stock prices, and liquidity has no effect on stock prices.